2004
DOI: 10.1080/0144929041000669941
|View full text |Cite
|
Sign up to set email alerts
|

The acceptance of a computerised decision-support system in primary care: A preliminary investigation

Abstract: Within the framework of technology acceptance modelling (Davis 1993), this study investigated the acceptance of a computerised decision-support system in primary care. Thirty general practitioners (GP) completed a questionnaire that detailed potential advantages of the system. A majority (70%) of GPs intended to use the system with a 2-min increase in consultation times (for proportion of GPs intending to use, CI 0.95 = [0.54; 0.85]) and eight advantages of the system were predictors of intention to use (R L 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Barriers such as cost should be included in future adoption models. Hence, similar to Van Schaik's (2004) conclusions, the results regarding payment also suggest that user acceptance research should consider a balance between benefits (e.g., usefulness) and barriers (e.g., costs).…”
Section: Conclusion and Discussionsupporting
confidence: 57%
“…Barriers such as cost should be included in future adoption models. Hence, similar to Van Schaik's (2004) conclusions, the results regarding payment also suggest that user acceptance research should consider a balance between benefits (e.g., usefulness) and barriers (e.g., costs).…”
Section: Conclusion and Discussionsupporting
confidence: 57%
“…Few have done this kind of beliefs elicitation work with respect to health IT [70, 72, 76, 96, 102], and none to our knowledge have revised TAM based on such work 3. Yet guides on how to carry out such work are readily available [42, 142, 146].…”
Section: Discussionmentioning
confidence: 99%
“…These models offer a potential explanation for how expectations of performance, effort, social influences, and facilitating conditions are determinants of user acceptance and technology usage [12]. Using the TAM, Van Schaik et al [13] evaluated a gastroenterology referral CDSS. The system assisted primary care providers by suggesting an appropriate subspecialty referral (medical vs surgical), prioritizing urgency, and offering real-time booking [13].…”
Section: Introductionmentioning
confidence: 99%
“…Using the TAM, Van Schaik et al [13] evaluated a gastroenterology referral CDSS. The system assisted primary care providers by suggesting an appropriate subspecialty referral (medical vs surgical), prioritizing urgency, and offering real-time booking [13]. They found that physicians rated acceptance based on the potential merits of the system rather than their experience with the computer system [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation